A boundary value problem in the hyperbolic space - P. Amster; G. Keilhauer; M. C. Mariani (Abstract and Applied Analysis)
We consider a nonlinear problem for the mean curvature equation in the hyperbolic space with a Dirichlet boundary data g. We find solutions in a Sobolev space under appropriate conditions on g.